The dopaminergic reward system underpins gender differences in social preferences. (November 2017) - Soutschek, Alexander; Burke, Christopher; Raja Beharelle, Anjali; Schreiber, Robert; Weber, Susanna; Karipidis, Iliana; ten Velden, Jolien; Weber, Bernd; Haker, Helene; Kalenscher, Tobias; Tobler, Philippe
Abstract Women are known to have stronger prosocial preferences than men, but it remains an open question as to how these behavioural differences arise from differences in brain functioning. Here, we provide a neurobiological account for the hypothesized gender difference. In a pharmacological study and an independent neuroimaging study, we tested the hypothesis that the neural reward system encodes the value of sharing money with others more strongly in women than in men. In the pharmacological study, we reduced receptor type-specific actions of dopamine, a neurotransmitter related to reward processing, which resulted in more selfish decisions in women and more prosocial decisions in men. Converging findings from an independent neuroimaging study revealed gender-related activity in neural reward circuits during prosocial decisions. Thus, the neural reward system appears to be more sensitive to prosocial rewards in women than in men, providing a neurobiological account for why women often behave more prosocially than men. Women often behave more prosocially than men. Soutschek et al. use pharmacology and neuroimaging to show that the neural reward system appears to be more sensitive to prosocial rewards in women than men, providing a neurobiological account for this gender difference.